2017
DOI: 10.22401/jnus.17.3.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Insecticides on the Egg Parasitoid, Trichogramma evanescens Westwood (Hymenoptera: Trichogrammatidae)

Abstract: In this study, the effects of three insecticides including: Fenvalerate, Thiacloprid and Fenoxycarb on egg parasitoid, Trichogramma evanescens were investigated. The toxicity of insecticide were tested using two laboratory tests: (a) direct spray on Ephestia cautella eggs containing the parasitoid for effects on parasitism and emergence of the adult parasitoids (b) adult parasitoid exposure to dry insecticide films residue in glass vials. All insecticides were prepared according to the manufacturer's recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…colemani. In another study, thiacloprid was tested on Trichogramma evanescens (Westwood) (Hymenoptera: Trichogrammatidae) and reduced adult emergence and parasitism by this species, although other species of this genus may not be as strongly affected (Abdulhay & Rathi, 2014). Bastos et al (2006) The sublethal effects of insecticides on insect pests are an important consideration when selecting an insecticide.…”
Section: Discussionmentioning
confidence: 99%
“…colemani. In another study, thiacloprid was tested on Trichogramma evanescens (Westwood) (Hymenoptera: Trichogrammatidae) and reduced adult emergence and parasitism by this species, although other species of this genus may not be as strongly affected (Abdulhay & Rathi, 2014). Bastos et al (2006) The sublethal effects of insecticides on insect pests are an important consideration when selecting an insecticide.…”
Section: Discussionmentioning
confidence: 99%
“…(2016) reported that thiacloprid + deltamethrin had the most negative impact on the life-table parameters of Lysiphlebus fabarum (Marshall) (Hymenoptera: Aphididae). In another study, Abdulhay and Rathi (2014) reported that thiacloprid reduced adult emergence and parasitism potency in Trichogramma evanescens (Westwood) (Hymenoptera: Trichogrammatidae).…”
Section: Discussionmentioning
confidence: 99%
“…However Ko et al, (2015) [11] reported thiamethoxam as "Slightly harmful" when treated at larval stage of Trichogramma with 33.2 reduction in adult emergence and also recorded 22.3 per cent reduction when treated with buprofezin after four days (larval stage) of parasitisation. Abdulhay et al, (2014) [1] observed thiacloprid as slightly harmful with 60.75 per cent reduction in adult emergence due to larvicidal and ovicidal activity with weaker adulticidal activity towards Trichogramma minutum. Madhusudhanan et al, (2014) [12] studied toxicity of flubendiamide 20 WG at 50, 60 and 70 g a.i.…”
Section: Effect On Uv Irradiated Eggs Of Corcyra Cephalonica Eggs Treated After 3 Rd Day Of Parasitisation By T Japonicummentioning
confidence: 99%